Application of Biourin and Mycorrhizal Fertilizers on the Dynamics of Available P, P Uptake, and Shallot (Allium ascalonicum L.) Yield in Vertisols - Rupa Matheus; Donatus Kantur (The University of Lampung, 2023)
The aim of this study was to evaluate the effect of application of biourin fertilizer and Mycorrhizal Vesicles Arbuscula (MVA) dosage on P dynamics, P uptake and yield of shallots in vertisols. This study was designed with a factorial design pattern on the basis of a randomized block design (RBD). The treatment tested was the concentration of biourin (B), with four levels: B10: Concentration of 10 ml.l-1 water, B20: Concentration of 20 ml.l-1 water, B30: Concentration of 30 ml.l-1 of water and B40: Concentration 40 ml.l-1 of water. The second treatment was MVA dose with four levels, namely: M0: Without MVA, M10:10 g.plant-1, M20: 20 g.plant-1 and M30: 30 g.plant-1. The results showed that the biourin concentration of 40 ml.l-1 of water and the MVA dose of 30 g.plant-1 significantly affected the dynamics of available P in Vertisol. The application of biourin at a concentration of 30 ml.l-1 water showed a P absorption of 15.07% and increased shallot yields by 41.07%. The best application of MVA biofertilizer in vertisols was achieved at a dose of 30 g.plant-1, able to increase plant nutrient P uptake by 152% and increase shallot yield by 72.38% from without MVA.Keywords: Concentration of biourin; MVA dose; P dynamics, Shallot yield